Exploring the anticonvulsant potential of Daucus carota L.: A combined in silico and in vivo study for epilepsy therapy development - Naznin Sarkar; Anil Kumar Venkategowda Kodihally; Akshay Shamnewadi (Pharmacological Research - Modern Chinese Medicine)
Background: Epilepsy is a neurological disorder characterized by recurrent seizures that significantly impact quality of life. Current treatments rely on conventional antiepileptic drugs (AEDs), which often present limitations such as inadequate efficacy, severe side effects, and the potential for drug resistance. This underscores the need for alternative therapies. This study aimed to explore the therapeutic potential of phytoconstituents from Daucus carota L. [the Chinese name: 胡萝卜, hú luó bo)] as a novel approach for epilepsy treatment. Methods: We adopted a comprehensive methodology integrating both in silico and in vivo approaches. Bioinformatic techniques, including gene set enrichment, network pharmacology using KEGG pathway analysis and Cytoscape tool and molecular docking using PyRx and Discovery studio tools, were employed. Additionally, LC‒MS analysis was performed to characterize the phytoconstituents present in the ethanolic extract. In vivo evaluations were conducted via the maximal electroshock (MES) model in Swiss albino mice to assess the anticonvulsant effects of the extract and combination therapy with phenobarbital sodium (PBT). Results: Molecular docking revealed significant binding affinities for apigenin (-6.7 kcal/mol) and luteolin (-6.6 kcal/mol) with GABRA1, suggesting their potential to enhance GABAergic signaling. LC‒MS analysis confirmed the presence of key bioactive compounds identified through in silico studies. The ethanolic extract yielded a substantial amount of bioactive compounds and demonstrated significant efficacy in the MES model by reducing seizure duration at a dose of 400 mg/kg (p < 0.01). Combination therapy with phenobarbital further enhanced the anticonvulsant effects, particularly in reducing extensor activity and clonus (p < 0.001). Conclusion: These findings suggest that phytoconstituents from Daucus carota L. possess significant therapeutic potential as adjunctive treatments for epilepsy through the modulation of GABAergic activity and calcium channel function. These results provide a compelling rationale for further preclinical and clinical investigations into the efficacy and safety of these natural compounds in the treatment of epilepsy.